Formulation and Physicochemical Characterization of Lycopene-Loaded Solid Lipid Nanoparticles - Elham Nazemiyeh; Morteza Eskandani; Hossein Sheikhloie; Hossein Nazemiyeh (Tabriz University of Medical Sciences, 2016)
Purpose: Lycopene belongs to the carotenoids that shows good pharmacological properties including antioxidant, anti-inflammatory and anticancer. However, as a result of very low aqueous solubility, it has a limited systemic absorption, following oral administration. Methods: Here, we prepared a stable lycopene-loaded solid lipid nanoparticles using Precirol® ATO5, Compritol 888 ATO and myristic acid by hot homogenization method with some modification. The size and morphological characteristics of nanoparticles were evaluated using Scanning Electron Microscopy (SEM). Moreover, zeta potential and dispersity index (DI) were measured using zeta sizer. In addition, encapsulation efficiency (EE%), drug loading (DL) and cumulative drug release were quantified. Results: The results showed that the size and DI of particles was generally smaller in the case of SLNs prepared with precirol when compared to SLNs prepared with compritol. Scanning electron microscopy (SEM) and particle size analyses showed spherical SLNs (125 ± 3.89 nm), monodispersed distribution, and zeta potential of −10.06 ± 0.08 mV. High EE (98.4 ± 0.5 %) and DL (44.8 ± 0.46 mg/g) were achieved in the case of nanoparticles prepared by precirol. The stability study of the lycopene-SLNs in aqueous medium (4 °C) was showed that after 2 months there is no significant differences seen in size and DI compared with the fresh formulation. Conclusion: Conclusively, in this investigation we prepared a stable lycopene-SLNs with good physicochemical characteristic which candidate it for the future in vivo trials in nutraceutical industries.